Performance of Bearings Combining Ceramic and Steel Rolling Elements - Alexander R. Gabelli (Tribology Online)
A balanced ceramic hybrid bearing incorporates an optimal mix of ceramic and steel rolling elements, balancing performance with manufacturing costs, which is crucial for many industrial products. The performance, tribological aspects and working mechanisms of balanced ceramic hybrid bearings are studied in detail based on an analysis of published data and further assessments. Balanced ceramic bearing’s static and dynamic load capacities are discussed and related to current bearing standards. A method for rating the lifespan of balanced ceramic hybrid bearings is proposed and validated using endurance test data. The fatigue life calculation allows for an assessment of the performance of this design against current solutions. The new calculation method is exemplified through a bearing application case. Bearing applications that can benefit from balanced ceramic bearings are identified, and their market potential is explored.